2014
DOI: 10.3109/03009742.2013.868509
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body magnetic resonance imaging in the assessment of muscular involvement in juvenile dermatomyositis/polymyositis patients

Abstract: WBMRI allows us to evaluate the extent and symmetry of muscle disease and inflammatory activity. NFC is an important additional examination to assess disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
0
12
0
4
Order By: Relevance
“…Edema is more diffuse in patients with dysferlinopathy, and patchy inflammation is more common in patients with inflammatory myopathies. 25 We demonstrated a correlation between the severity of fatty infiltration and clinical assessments, indicating that fatty infiltration is sensitive for monitoring disease progression. Although it is believed that the severity of muscle edema correlates with clinical severity in inflammatory myopathies, 26 we and others 27 did not find a correlation between muscle edema and clinical assessments (both at the individual muscle level and when taking muscle groups in the thigh as a whole).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Edema is more diffuse in patients with dysferlinopathy, and patchy inflammation is more common in patients with inflammatory myopathies. 25 We demonstrated a correlation between the severity of fatty infiltration and clinical assessments, indicating that fatty infiltration is sensitive for monitoring disease progression. Although it is believed that the severity of muscle edema correlates with clinical severity in inflammatory myopathies, 26 we and others 27 did not find a correlation between muscle edema and clinical assessments (both at the individual muscle level and when taking muscle groups in the thigh as a whole).…”
Section: Discussionmentioning
confidence: 73%
“…However, the pattern of muscle edema is different. Edema is more diffuse in patients with dysferlinopathy, and patchy inflammation is more common in patients with inflammatory myopathies …”
Section: Discussionmentioning
confidence: 99%
“…In our study, sensitivity increased to 95% when all five enzymes were tested, and MRI increased the sensitivity further. One study by Castro et al used whole‐body MRI (WB‐MRI) to assess for myositis in a panel of JDM and polymyositis patients and found that all patients with positive WB‐MRI had at least one abnormal muscle enzyme. The increased sensitivity in our series may be due to the use of a focal MRI of the gluteal and proximal thigh muscles in contrast to the WB‐MRI, which has lower resolution due to its wider field of view.…”
Section: Discussionmentioning
confidence: 99%
“…Current MRI protocols usually include both T1‐weighted and water‐sensitive sequences, such as inversion recovery pulse sequences, to assess fatty atrophy and depict muscle edema (ME), respectively . Whole‐body MRI (WB‐MRI) is advantageous because it allows multiple muscles to be explored and muscle groups with subclinical disease to be detected, and it permits muscle biopsies to be targeted to areas of ME . However, inflammatory changes have been found in biopsies of muscles without ME in MRI, suggesting that a certain level of inflammation is required for detection by conventional imaging sequences …”
mentioning
confidence: 99%
“…2 Whole-body MRI (WB-MRI) is advantageous because it allows multiple muscles to be explored and muscle groups with subclinical disease to be detected, and it permits muscle biopsies to be targeted to areas of ME. [3][4][5][6] However, inflammatory changes have been found in biopsies of muscles without ME in MRI, suggesting that a certain level of inflammation is required for detection by conventional imaging sequences. 7 Unlike standard MRI sequences, the signal in diffusion-weighted imaging (DWI) depends on the random movement of water molecules.…”
mentioning
confidence: 99%